Ten years of Spanish criminal law against gender violence: habitual abuse and occasional abuse in the couple (2016)
The criminal provisions of the Organic Law 1/2004, on Comprehensive Measures against Gender Violence (the “Comprehensive Law”)  —in force since 30 June 2005—, represent a turning point regarding punishment of the violence inflicted on a woman by her male